45P 5-AZA treatment induces cytotoxicity and in vitro expression of immunogenic NY-ESO-1 antigen in non-small lung cancer cell NCI-H1975. (15th December 2019) - Inchakalody, V P; Taleb, S; Sherif, S; Fernandes, Q; Sahir, F; Sivaraman, S K; Khan, A Q; Nair, V Sasidharan; Ashi, E A A; Al-Zaidan, L S; Iskandarani, A; Krishnankutty, R; et al.
Abstract: Background: Lung cancer is a major threat to the world and 80% of the reported cases belong to non-small cell lung cancers. Epigenetic modifications are common in lung cancers but can be reversible by using demethylating agents such as 5-AZA. Through our present study, we hypothesized that treatment with 5-AZA may induce the apoptosis and expression of immunogenic NY-ESO-1 antigen in NCI-H1975 cells. Apoptotic cell death would help to release the induced NY-ESO-1 protein which in turn could trigger T cells mediated immune responses. Methods: NCI-H1975 cells were treated with incrementing concentrations (1 to 10µM) of 5-AZA. Cytotoxicity was measured using real-time cell analyzer assay (RTCA). Apoptosis and cell cycle analysis were measured by flow cytometry and western blot. A proteomic profiling was carried out using label-free mass spectrometry. Bisulfite sequencing was performed for NY-ESO-1 gene and expression at mRNA and protein level was analyzed using qRT-PCR, cellular ELISA. Results: RTCA data revealed that 5-AZA treatment reduced cell proliferation at 120 h which was opted for comparative study. Flow cytometry showed an induction of apoptosis and a cell-cycle arrest at Sub-G0 phase. Western blot analysis confirmed the induction of apoptotic marker proteins such as cleaved Caspase3, Caspase8, PARP and BAX. We also observed that 31 proteins responsible for the induction of apoptosis were upregulated and 18 proteins linked to cell proliferation and metastasis were down-regulated. Bisulfite sequencing revealed demethylation of the promoter of NY-ESO-1 gene and showed an induced expression of NY-ESO-1 protein and mRNA levels. Conclusion: Our study shows that 5-AZA cytotoxic effect would induce the expression of the immunogenic NY-ESO-1 antigen leading to activation of T cells mediated immune response. Our data infers the potential use of 5-AZA for lung cancer treatment. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.